2009
DOI: 10.1016/j.metabol.2008.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The response of γ vitamin E to varying dosages of α vitamin E plus vitamin C

Abstract: Background Vitamin E has been studied extensively in the prevention of atherosclerosis. Cross-sectional population studies as well as randomized controlled intervention trials have demonstrated conflicting results. A recent meta-analysis of these trials has emphasized the ineffectiveness of vitamin E in atherosclerosis prevention with a possibility of harm at higher dosages. However, vitamin E has several isomers, with the alpha form being available via dietary supplements and the gamma form being available vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 77 publications
2
19
0
1
Order By: Relevance
“…Chen et al [43] found nonsignificant changes in FBS or insulin concentration after the intake of VC in diabetic patients with inadequate levels of vitamin. In contrast, coadministration of vitamins C and E in T2DM for 14 days did not show any improvement in BG, insulin, c-peptide and surrogate markers of atherosclerosis or inflammation [60]. In addition, the protective effect of VC against NO was not observed in subjects with diabetes [43], which may indicate that VC produces beneficial effects when administered during the early onset of CVD [61].…”
Section: Discussionmentioning
confidence: 92%
“…Chen et al [43] found nonsignificant changes in FBS or insulin concentration after the intake of VC in diabetic patients with inadequate levels of vitamin. In contrast, coadministration of vitamins C and E in T2DM for 14 days did not show any improvement in BG, insulin, c-peptide and surrogate markers of atherosclerosis or inflammation [60]. In addition, the protective effect of VC against NO was not observed in subjects with diabetes [43], which may indicate that VC produces beneficial effects when administered during the early onset of CVD [61].…”
Section: Discussionmentioning
confidence: 92%
“…Platelet aggregation was 16% lower in rats fed α-tocopherol and 43% lower in rats fed γ-tocopherol as compared with controls. 40 In humans, α-tocopherol supplementation alone reduced serum γ-tocopherol levels, 41 while a supplement with equal amounts of α- and γ-tocopherols raised plasma α- and γ-tocopherol levels. 42 A supplement with mixed tocopherols (100 mg γ-, 40 mg δ-, and 20 mg α-tocopherol; corresponding to a 20 mg α-tocopherol equivalent) reduced platelet aggregation by 14% as compared with pre-supplementation platelet aggregation values.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, epidemiological evidence suggests that the protective effect of vitamin E against AD can be due to the contribution of its different forms, while intake of high doses of a-tocopherol can decrease the bioavailability of the other congeners potentially increasing mortality risk [77][78][79]. Indeed, epidemiological evidence suggests that the protective effect of vitamin E against AD can be due to the contribution of its different forms, while intake of high doses of a-tocopherol can decrease the bioavailability of the other congeners potentially increasing mortality risk [77][78][79].…”
Section: Vitamin E and Ad: Clinical Evidencementioning
confidence: 99%